The Implementation of Health Promotion: A New Structural Perspective - Rütten, Alfred (Social science & medicine, 1995)
Although health promotion has become a critical concept in public health, both research and practical projects in this area are almost devoid of theory. The present article uses a theory of complexity and structure to organize the different elements of health promotion in a new perspective. This perspective involves (1) new ways for looking at patterns of behavioral risk factors and health-related lifestyles. It (2) relates health promotion to policy making. In particular, it (3) focuses on a comprehensive model of the implementation process, revealing the true interrelationship of relevant elements to the concept of health promotion. In this context, it (4) becomes obvious that the reflexivity and recursiveness of scientific analyses are an integral part of the structure of health promotion. Thus, the professional role of the social scientist with regards to the implementation and utilization of scientific knowledge in the field of public health policy will be discussed. Finally, the role of appropriate theory is emphasized as a strategy for improving the practice of health promotion and to further the development of a new public health. © 1995.
UnivIS-Import:2015-03-05:Pub.1995.phil.dps.iss.lsw.theimp
Keywords: applied science; health promotion; implementation model; lifestyle; policy analysis